The Effect of Loyalty Programs, Product Quality, and Satisfaction on Customer Loyalty in Small and Medium Entreprises - Chandya, Chandya; Murhadi, Werner R. (Journal of Entrepreneurship & Business, 2026)
Purpose: The purpose of this study is to examine the impact of loyalty programs and product quality on customer satisfaction and loyalty in small and medium-sized enterprises (SMEs). This study investigate the effect of loyalty program, programs and product quality on customer satisfaction and loyalty in small and medium-sized enterprises. This research aims to contribute to small and medium-sized businesses by offering loyalty programs tailored to their business capabilities, thereby increasing customer satisfaction and loyalty. Method: This study investigates the influence of loyalty programs and product quality on customer satisfaction and loyalty, employing a structural equation modeling approach. The population of this study is all customers who buy Baby diapers products for their children to wear. The sampling technique used is non-probability sampling with purposive sampling and the number of respondents collected is 104 respondent. Result: The results showed a significant positive effect of loyalty programs on customer satisfaction and a significant positive effect of product quality on customer loyalty. This study did not find any mediating role of customer satisfaction. Companies can implement loyalty programs to enhance customer satisfaction, improve product quality, and foster customer loyalty. This study contributes to the literature by combining the concepts of product quality and loyalty programs that SMEs can develop to create customer satisfaction and loyalty.